The Effect of Ease of Access to Services and Transparency of Information on Population Service Satisfaction - Maman Musa; Darman; Sadam Yunus (West Science Interdisciplinary Studies, 2023)
This research was conducted to determine the effect of Ease of Service Access and Information Transparency on Population Service Satisfaction in Gorontalo. The sampling technique used was Accidental Sampling by determining 51 respondents. The research method uses quantitative descriptive with the Statical program for social science (SPSS). The results of this study show that Ease of Service Access and Information Transparency significantly affect Population Service Satisfaction with a calculated F value of 58.409, with a total influence of 0.704 or 70.4%. Ease of access to services has a significant effect on population service satisfaction with a calculation value of 4,670, information transparency has a significant effect on population service satisfaction with a calculation value of 2,495.